SISTEM PEMANTAUAN KONSENTRASI CO KEBAKARAN HUTAN RIAU MENGGUNAKAN TEKNOLOGI WIRELESS SENSOR NETWORK (WSN) DAN INTERNET OF THINGS (IOT) - Eko Prayitno; Desi Amirullah (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
The purpose of this research is how to make an air condition monitoring system by considering the concentration value of carbon monoxide in Riau Province. The technology used to support monitoring system of carbon monoxide concentration, using Wireless Sensor Network Technology (WSN) and Internet of Things (IoT). One of the WSN concepts to be used is a combination of several sensors, the only sensors used to detect the level of carbonmonoxide concentration include: carbon monoxide, temperature and humidity sensors. Air condition data derived from the sensor in the form of concentration value of carbon monoxide, temperature and humidity of air sent to server connected to network using IoT technology. Based on the test results it can be concluded that the air condition monitoring system using WSN and IoT technology can be applied in realtime, this can be proven with the data shown in the monitoring tool. the detection of a fire source using a sensor can be done by using a distance between a smoke source (hotspot) and a device 90cm. From the observation result there is difference between sensing data without smoke and using smoke, such as temperature has 60C difference, humidity 20 rh and carbon monoxide about 17ppm